Genistein Antagonizes 17β-Estradiol Effects on Glutamate-Evoked Masseter Muscle Hypernociception in Rats - Jie, Hui-Fei; Yang, Guang-Ju; Bi, Rui-Yun; Mo, Si-Yi; Gan, Ye-Hua; Xie, Qiu-Fei (Frontiers in Neurology, 2018)
Temporomandibular disorders (TMDs) predominantly affect women of reproductive ages, with pain as the main symptom. The aim of the present study was to examine the effects of 17β-estradiol (E2) on glutamate-evoked hypernociception of masseter muscle and to examine whether genistein could antagonize the effects of E2 in female rats. Injection of glutamate into the masseter muscle dose-dependently decreased head withdrawal thresholds, a parameter for mechanical hypernociception. Head withdrawal thresholds in ovariectomized rats also decreased with increasing doses of E2 replacement, and were further aggravated by injection of glutamate (1M, 40μL) into the masseters. Genistein at doses of 7.5 and 15 mg/kg antagonized E2-induced hypernociception of masseter muscle, and at doses of 7.5, 15, and 30 mg/kg also antagonized E2 potentiation of glutamate-evoked hypernociception of masseter muscle. Genistein produced optimal antagonistic effects of E2 on nociception behavior at a dose of 15 mg/kg. On the molecular level, tyrosine phosphorylation of the NR2B subunit of the N-methyl-D-aspartate receptor (pNR2B) and phosphorylated mitogen-activated protein kinase (pERK1/2) were significantly upregulated in the hippocampus following glutamate injection and were further potentiated by E2 replacement. Genistein at dose of 15 mg/kg partially reversed E2-potentiated glutamate-evoked upregulation of pNR2B and pERK1/2 expression in the hippocampus. These results indicated that moderate doses of genistein could antagonize E2 enhanced glutamate-evoked hypernociception of masseter muscle possibly via N-methyl-D-aspartate receptor and ERK1/2 signaling pathways in the hippocampus.